Faktor-Faktor Yang Mempengaruhi Persepsi Dan Pemahaman Tentang Produk Pembiayaan Syariah Pada Karyawan Perbankan Syariah Di Indonesia - Masriyanda Masriyanda (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2017)
Research in this paper attempts to examine the influence of knowledge about Islamic bank product, the basic principles of Islamic banking, training and religiosity to perceptions and understanding of Islamic bank financing products. Research conducted on employees in some Islamic banks in Indonesia, the banks participating in this study were Bank Muammalat Indonesia, Bank BNI Syariah, Bank BTN Syariah, Bank BRI Syariah, Bank BPD DIY sharia and Bank Sulselbar Sharia. Quantitative data were processed using SPSS 20.0 statistical software. using multiple linear regression analysis. The results illustrate that the knowledge of Islamic bank products and training influence the perception and understanding of Islamic bank financing products. While the basic principles of Islamic banking and religiosity have no influence on perception and understanding of Islamic bank financing products.